Catechin Hydrate Mitigates DEHP Toxicity by Attenuating Oxidative Stress in Mesenchymal Stem Cells: Catechin hydrate prevents oxidative stress induced by DEHP - Abnosi, Mohammad Hussein; Ahmadi, Zahra (Iranian Journal of Pharmaceutical Sciences, 2026)
Since di-2-ethylhexyl phthalate (DEHP) from medical bags and tubes induces oxidative stress in bone marrow mesenchymal stem cells (BMSCs). Therefore, the aim was to use Catechin hydrate (CH) as a natural antioxidant to prevent lipid peroxidation. In this experimental study, BMSCs were treated with 0.063, 0.125, 0.25, 1, and 10 μM of CH for 4 days. Based on its effect on cell viability, 0.25 μM of CH was selected for further analysis. The cell was treated with 0.25 μM of CH as well as 100 and 500 μM of DEHP individually and in combination for 4 and 8 days to study cell viability, population doubling number (PDN), total protein, malondialdehyde (MDA), total antioxidant capacity (TAC), catalase (CAT) and superoxide dismutase (SOD) activity, nucleus and cytoplasm morphology and expression of Nrf2 and NFkB genes. Viability and proliferation ability of BMSCs were significantly (p<0.0001) decreased by DEHP in a dose and time-dependent manner, while CH caused a significant increase (P<0.0001). DEHP decreased (P < 0.0001) total protein, TAC, and the activity of antioxidant enzymes, and increased (P < 0.001) the MDA level, as well as causing morphological changes. In addition, DEHP caused a significant decrease in NF-κB and an increase in Nrf2 expression. Although CH in simultaneous treatment was able to completely compensate for the toxic effect of DEHP at 100 μM, especially at 8 days, when compared to the control, it could not prevent the toxic effect at 500 μM. In addition, CH was able to compensate for the imbalance of the NFkB/Nrf2 caused by DEHP. The consumption of fruits, vegetables, and especially tea, which contains a low concentration of CH, may be an alternative medicine for patients undergoing hemodialysis and blood transfusion.